Pelaksanaan Kegiatan Posyandu Dalam Meningkatkan Kesehatan Batita Di Posyandu Sakura RW 03 Cihaurgeulis Bandung - Aulia Zeta Andhani; Sali Setiatin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aims to study the implementation of Posyandu activities in improving toddler health through activities. This type research is quantitative survey. They population is all of the people of RW 03 Cihaurgeulis who have toddlers with as many as 22 peoples, samples taken 100% of the population. The technique of collecting data uses a questionnaire. Data collection tool uses questionnaire sheets. The data analysis technique uses the precentage formula. The result of the research show how the implementation of Posyandu activities in improving toddler health in RW 03 Cihaurgeulis kota Bandung through activities (a) weighing the implementation is always, (b) heighting the implementation is always, (c) progress monitoring the implementation is always, (d) administration of vitamin A is done always, (e) immunization is done always, (f) monitoring the incidence of ISPA and diarrhea programs sometimes, also seen from (g) the healthof children (healthy children), there are not children experiencing health problems so that they are categorized as healthy children.